2019
DOI: 10.1242/dev.172734
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin B2 is required for progression through meiosis in mouse oocytes

Abstract: Cyclins associate with cyclin-dependent serine/threonine kinase 1 (CDK1) to generate the M phase-promoting factor (MPF) activity essential for progression through mitosis and meiosis. Although cyclin B1 (CCNB1) is required for embryo development, previous studies concluded that CCNB2 is dispensable for cell cycle progression. Given previous findings of high Ccnb2 mRNA translation rates in prophasearrested oocytes, we re-evaluated the role of this cyclin during meiosis. Ccnb2 −/− oocytes underwent delayed germi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 47 publications
0
41
0
Order By: Relevance
“…The authors suggest that the metaphase I arrest observed in a significant proportion of Ccnb2-/oocytes is due to SAC activation because inhibition of the essential SAC kinase Mps1 can rescue polar body extrusion. Ccnb2-/oocytes that fail to extrude a polar body show kinetochore recruitment of the SAC component Mad2 indicating prolonged SAC activation, even though under normal conditions the SAC is activated only very transiently in meiosis I (Daldello et al 2019). A small caveat of this assay is the fact that without a functional SAC, oocytes undergo metaphase-to-anaphase transition precociously and with much lower Cdk1 activity (Touati et al 2015;Rattani et al 2014).…”
Section: Complete Loss Of Either Cyclin B1 or B2 In Mouse Oocytesmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors suggest that the metaphase I arrest observed in a significant proportion of Ccnb2-/oocytes is due to SAC activation because inhibition of the essential SAC kinase Mps1 can rescue polar body extrusion. Ccnb2-/oocytes that fail to extrude a polar body show kinetochore recruitment of the SAC component Mad2 indicating prolonged SAC activation, even though under normal conditions the SAC is activated only very transiently in meiosis I (Daldello et al 2019). A small caveat of this assay is the fact that without a functional SAC, oocytes undergo metaphase-to-anaphase transition precociously and with much lower Cdk1 activity (Touati et al 2015;Rattani et al 2014).…”
Section: Complete Loss Of Either Cyclin B1 or B2 In Mouse Oocytesmentioning
confidence: 99%
“…Below we introduce progression through the meiotic divisions (meiotic maturation) from a cell cycle point of view, before describing the roles of the three existing mammalian B-type cyclins B1, B2 and B3 (Nieduszynski, Murray, and Carrington 2002;Chapman and Wolgemuth 1992;Pines and Hunter 1989), all three of which have now been studied by knock-out approaches in mouse oocytes J. Li et al 2018;Daldello et al 2019;Y. Li et al 2019;Brandeis et al 1998).…”
Section: Mammalian Meiosismentioning
confidence: 99%
See 3 more Smart Citations